2019
DOI: 10.1002/ams2.469
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of jellyfish stings in Japan

Abstract: Aim: Jellyfish known as "habu-kurage" (Chironex yamaguchii) inhabit the waters surrounding Okinawa and Amami, Japan, and jellyfish stings are limited to areas outside the Japanese main island. However, the shifts promoted by global warming and increasingly intensive interactions with people have led to concerns regarding the possibility of increased jellyfish stings on the main island of Japan. Similar concerns are being raised all over the world. However, studies examining clinical characteristics of jellyfis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
(17 reference statements)
0
7
1
Order By: Relevance
“…5 This suggests that there is an unmet need for public health interventions and appropriate prehospital management in Japan. Unlike in our current examination of jellyfish stings in Japan, 8 in the current study, there were no significant differences observed between tourist and non-tourist groups with regard to baseline characteristics. A possible reason for this result could be that, owing to the severe pain caused by the stonefish venom verrucotoxin, patients (tourists and nontourists) tended to promptly visit the emergency department.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…5 This suggests that there is an unmet need for public health interventions and appropriate prehospital management in Japan. Unlike in our current examination of jellyfish stings in Japan, 8 in the current study, there were no significant differences observed between tourist and non-tourist groups with regard to baseline characteristics. A possible reason for this result could be that, owing to the severe pain caused by the stonefish venom verrucotoxin, patients (tourists and nontourists) tended to promptly visit the emergency department.…”
Section: Discussioncontrasting
confidence: 99%
“…11 The basic questionnaire was distributed in February 2019 and collected by March 2019. 8 The advanced questionnaire 1 was distributed to two hospitals that had treated patients with severe stonefish envenomation, as stated in the basic questionnaire. The advanced questionnaire 1 was distributed in May 2019 and collected by July 2019.…”
Section: Patients and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiology: Jellyfish appear in large numbers in swimming areas, particularly inlets and beaches where waves are subdued. Several jellyfish sting cases have been reported in the literature [10][11][12] and recently, Hifumi et al comprehensively described the clinical characteristics of jellyfish stings in Japan [13]. One urban emergency department in Hawaii experiences approximately 20 jellyfish sting cases annually [14].…”
Section: Box Jellyfishmentioning
confidence: 99%
“…Diagnosis: No definite diagnostic criteria exist. Diagnosis of jellyfish stings is based on either the patient's history or positive identification of the responsible jellyfish presented by the patient [13]. Severe stings result in systemic envenomation, which may result in Irukandji syndrome and/or anaphylaxis, and most often require hospital admission [15].…”
Section: Box Jellyfishmentioning
confidence: 99%